Netter s atlas of neuroscience /David L. Felten, MD, PhD, M. Kerry O Banion, MD, PhD, Mary Summo Maida, PhD; illustrations by Frank H. Netter, MD ; contributing illustrators, James A. Perkins, MFA, CMI, FAMI, Carlos A.G. Machado, MD, John A. Craig, MD. - Felten, David L.,author.
Includes bibliographical references and index.